A two-year field study and evaluation of water quality and trophic state of a large shallow drinking water reservoir in Shanghai, China. Issue 29 (20th June 2016) - Liu, Hongbo; Pan, Ding; Chen, Piao
Abstract: Reservoirs have been widely constructed all over the world in recent years to alleviate the shortage of water resources. Nevertheless, the assessment method of water quality and its trophic status needs to be developed. In this study, water quality parameters of a newly constructed shallow reservoir were regularly monitored for a period of two years, which is used as a major drinking water source of Shanghai, China. Furthermore, the trophic state indices of the reservoir were investigated based on literature and evaluated with the two-year field data. The results indicated that the studied reservoir is reaching the mesotrophic–eutrophic boundary, where further nutrient enrichment could cause water quality degradation; total phosphorus is the limiting nutrient for algal growth in the studied reservoir. Results of the study can help operators understand change and status of water quality of the reservoir and provide valuable data demonstrating variation of water quality indicators and trophic characteristics in shallow reservoirs or lakes.